2019
DOI: 10.20524/aog.2019.0378
|View full text |Cite
|
Sign up to set email alerts
|

The role of mast cells in pediatric gastrointestinal disease

Abstract: Mast cells are granulocytes derived from CD34+ pluripotent progenitor cells that demonstrate plasticity in their development, leaving the bone marrow and differentiating in the tissue where they ultimately reside. They are best known for their role in the allergic response, but also play a prominent immunoregulatory role in other processes, including immune tolerance, the innate immune response, angiogenesis, wound healing and tissue remodeling. Mast cells are found throughout the gastrointestinal tract; their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 70 publications
0
15
0
1
Order By: Relevance
“…Generally 1 H NMR spectra are obtained using a recycle delay of 5 s or less for quantitative analysis in the metabolomics field. 40 Use of a relaxation delay shorter than five times T 1 provides an advantage of high throughput measurement without affecting the inferences of studies, particularly when comparing two or more groups of samples as often encountered in the metabolomics field.…”
Section: Resultsmentioning
confidence: 99%
“…Generally 1 H NMR spectra are obtained using a recycle delay of 5 s or less for quantitative analysis in the metabolomics field. 40 Use of a relaxation delay shorter than five times T 1 provides an advantage of high throughput measurement without affecting the inferences of studies, particularly when comparing two or more groups of samples as often encountered in the metabolomics field.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomics is the study of small molecules that make up a network of metabolic pathways, and it provides key insights into gene-environment interactions. [19][20] Mass spectrometry (MS) and NMR techniques have been used extensively to study metabolomics. In the metabolomics field, MS is commonly used because of its high sensitivity, detection of many metabolites in a single measurement, and reliable metabolite identification through tandem mass analysis; however, MS is destructive to samples and the identities for a major fraction of detected metabolites are frequently not known.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Accumulating evidences indicated that the function of MCs in IBD is more complicated than originally thought, Animal and human clinical studies suggested that the contribution of these cells includes regulating epithelium permeability, immune signal transmittance, maintenance and resolution of inflammatory responses, and subsequent tissue remodeling [2,[30][31][32][33][34]. What's more, the study showed that the increase of MCs infiltration near the epithelium resulted in a favorable microenvironment that expressed more beneficial proteins including ZO-1, FGF2, ANGPTL2, REG3γ, and REG3β, which are involved in signal transduction, cell growth, tissue repair, and homeostasis maintenance [2].…”
Section: Discussionmentioning
confidence: 99%